Evaluation of Horticulture Oil for the Management of Tetranychus urticae Koch and Panonychus ulmi Koch On apple trees (Damascus University Journal of agriculture sciences, 2021)
The effect of mineral and plant –based horticulture spray oils was studied on the two main spider mites Panonychus ulmi Koch Tetranychus urticae Koch on two varieties of apples (Golden delicious and Starking delicious) in dormant and growing season for three years from 2018 to 2020. Summer oil was effective against the two spider mite species T. urticae and P.ulmi. No significant effects were found between two kinds of summer oil during the three seasons. Significant effects were found between the summer oils comparing to the check. The two kinds of dormant oils are reducing the numbers of the two kind of spider mite on the two varieties of apple during 2018-2019. Summer oils have more effect on the predatory mites from phytosiiedae than dormant oil. So, it can be used in integrated pest management because they are less harmful towards humans and environment than conventional acaricides.
Keywords: horticulture oils; apple; Tetranychus urticae; Panonychus ulmi; Phytosiiedae